Sistem Informasi Geografis Kerusakan Jalan Berbasis Web - Adhar, Adhar; Lakawa, Irwan; Sufrianto, Sufrianto (Universitas Sulawesi Tenggara, 2021)
According to the North Buton Regency Public Works and Spatial Planning Agency in the Central Statistics Agency (2020), in the North Buton Regency area there are still many roads that are slightly damaged or heavily damaged, the road damage is a very complex problem. The losses and impacts suffered are enormous for the road users, while mapping and research, especially on road conditions, are still lacking attention. Recognizing the need for information on road damage that can display the condition of provincial roads in North Buton Regency, the information system that will be displayed in the form of a digital map based on Geographical Information System (GIS) is more effective in providing visualization of road damage data, road conditions and reports of road damage, especially on provincial roads in North Buton Regency. The research objectives are: (1) To analyze the level of damage to provincial roads in North Buton Regency. (2) Knowing the WEB-based Geographical Information System Damage to Provincial Roads in North Buton Regency. The results of the analysis and discussion carried out resulted in the level of damage to the Provincial Roads in North Buton Regency using the PCI (method Pavement Condition Index)along 12 km which is divided per 300 meters into 40 segments. With the average value of 65 in the condition(Good)and then with a geographic information system (GIS) based WEB, data showed damage to the weathering of the surface as much as 31%, the hole as much as 39%, Cracks extends as much as 4%, Weathering granules off as much as 13% , Block crack by 2%, Bleeding as much as 9% and Amblast by 2%.